Intestinal PTGS2 mRNA Levels, PTGS2 Gene Polymorphisms, and Colorectal Carcinogenesis - Vogel, Lotte K. (Public Library of Science, 2014)
BACKGROUND & AIMS: Inflammation is a major risk factor for development of colorectal cancer (CRC). Prostaglandin synthase cyclooxygenase-2 (COX-2) encoded by the PTGS2 gene is the rate limiting enzyme in prostaglandin synthesis and therefore plays a distinct role as regulator of inflammation. METHODS: PTGS2 mRNA levels were determined in intestinal tissues from 85 intestinal adenoma cases, 115 CRC cases, and 17 healthy controls. The functional PTGS2 polymorphisms A-1195G (rs689466), G-765C (rs20417), T8473C (rs5275) were assessed in 200 CRC cases, 991 adenoma cases and 399 controls from the Norwegian KAM cohort. RESULTS: PTGS2 mRNA levels were higher in mild/moderate adenoma tissue compared to morphologically normal tissue from the same individual (P<0.0001) and (P<0.035) and compared to mucosa from healthy individuals (P<0.0039) and (P<0.0027), respectively. In CRC patients, PTGS2 mRNA levels were 8–9 times higher both in morphologically normal tissue and in cancer tissue, compared to healthy individuals (P<0.0001). PTGS2 A-1195G variant allele carriers were at reduced risk of CRC (odds ratio (OR) = 0.52, 95% confidence interval (95% CI): 0.28–0.99, P = 0.047). Homozygous carriers of the haplotype encompassing the A-1195G and G-765C wild type alleles and the T8473C variant allele (PTGS2 AGC) were at increased risk of CRC as compared to homozygous carriers of the PTGS2 AGT (A-1195G, G-765C, T8473C) haplotype (OR = 5.37, 95% CI: 1.40–20.5, P = 0.014). No association between the investigated polymorphisms and PTGS2 mRNA levels could be detected. CONCLUSION: High intestinal PTGS2 mRNA level is an early event in colorectal cancer development as it occurs already in mild/moderate dysplasia. PTGS2 polymorphisms that have been associated with altered PTGS2 mRNA levels/COX-2 activity in some studies, although not the present study, were associated with colorectal cancer risk. Thus, both PTGS2 polymorphisms and PTGS2 mRNA levels may provide information regarding CRC risk.